Biodegradation of manganese in sequencing batch reactor - Mohamad Zarqani, Yeop (2009)
This thesis is about the biodegradation of manganese in sequencing batch reactor. Biodegradation of manganese in sequencing batch reactor (SBR) is a new invention treatment method that gives a lot of advantage in term of lowering operation and maintenance cost. The works done in this research explore the effects of different loading rate (LR) on the water quality parameter. For this research, biofilm process was selected as a treatment method which is develop in the SBR. At the beginning of the experiment, the mixed cultured was collected from drain and acclimatized in 10 liter reactor and monitoring the growth by using suspended solid (SS) test. The mixed cultured was acclimatized within two months by fed with 1mg/L manganese. For the treatment process, the mixed culture from acclimatization reactor will be transferred to the treatment reactor. The manganese treatment process will be carried out by controlling the loading rate. The hydraulic retention time (HRT) selected for this research is 5 days. The experiment will be run within two weeks. Within this period, the collection of the sample will be done for everyday as well as the addition of the simulated wastewater to the treatment reactor. The data shown that the lowest organic loading rate which is 3mg/L.d giving the highest percent of manganese removal. The highest manganese removal is 65% while the highest value of chemical oxygen demand (COD) removal is 72% at 3.5 mg/L.d. By using the Design Expert, the predicted value will represent the optimization results for this research. The value for optimization is at lowest LR which is 3 mg/L.d. By using lowest LR, the treatment will get 43% of COD removal and 57% manganese removal. The optimization of concentration of suspended solid is 381 mg/L.